P213 The Prevalence and Impact of Gastro-Oesophageal Reflux Symptoms in Stable COPD Patients. (19th November 2012) - Patel, ARC; Kowlessar, BS; Donaldson, GC; Singh, R; Mackay, AJ; Brill, S; Wedzicha, JA; Hurst, JR
Abstract : Introduction: Gastro-oesophageal reflux disease (GORD) has been associated with increased COPD exacerbation frequency (Terada et al, Thorax 2008) and was independently associated with the frequent exacerbator phenotype in the ECLIPSE study (Hurst et al, NEJM 2010). We aimed to quantify the prevalence and impact of GORD in stable COPD in terms of airflow limitation, dyspnoea, health status and exacerbation frequency in a well-characterised cohort. Methods: Stable outpatients from the London COPD cohort completed the Frequency Scale for the Symptoms of Gastro-oesophageal reflux (FSSG), Hull Airway Reflux Questionnaire (HARQ), MRC dyspnoea score, and St George's Respiratory Questionnaire (SGRQ) during clinic visits. Spirometry was performed in accordance with ATS/ERS guidance. Comorbidities including GOR and all medications were recorded by clinical research staff. Exacerbations were defined using our usual symptomatic criteria from daily diary cards (Seemungal et al, AJRCCM 1998). Results: 156 stable COPD patients had a mean±SD age of 72.2±9.7 years, 63% male, 29% current smokers, median (IQR) 46 (25, 59) pack years, mean±SD FEV1 1.34±0.57L and 54.4±20.2%predicted, BMI 26.5±5.7kg/m2. 60 (38%) patients had a diagnosis of GORD, of whom 45 (75%) were taking regular acid suppression therapy (42 proton pump inhibitors, 3 H2 antagonists). COPD patients with GORD had a higher exacerbation frequency than those without (median (IQR) 2.0 (1.0, 3.4) vs 1.2 (0.0, 3.0) per year, p=0.028). In those with GORD, the use of acid suppression therapy did not impact exacerbation frequency (median (IQR) 2.0 (1.0, 4.0) (n=45) vs 2.0 (1.0, 3.0) (n=15) per year, p=0.431). FSSG and HARQ scores were both related to COPD exacerbation frequency (rho=0.159, p=0.050 and rho=0.185, p=0.021 respectively) and more strongly to SGRQ (r=0.425, p<0.001 and r=0.439, p<0.001 respectively). They were not related to MRC dyspnoea score (rho=0.079, p=0.367 and rho=0.126, p=0.148 respectively) or FEV1% predicted (r=–0.063, p=0.452 and r=–0.067, p=0.416 respectively). Conclusions: GORD is common in COPD and is associated with higher exacerbation frequency, although acid suppression therapy does not appear to affect this. Higher GORD symptom scores relate to worse health status and higher exacerbation frequency but not to airflow limitation or dyspnoea. Understanding the mechanisms may lead to novel effective interventions in COPD.